Space requirements of finishing pigs fed to a heavier weight (removed individually) - Fitzner, G.E.; Nichols, David A.; Hancock, Joe D.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Space allowances of 6, 8, 10, and 12 ft2 were evaluated for pigs fed from 120 to 250 lb. The management system used was to remove pigs individually as they reached 250 lb, which provided increasing space per pig. Using this management system, average daily gain, average daily feed intake, and feed efficiency improved linearly with increasing space allowance. Pigs allowed 6ft2 gained slower, ate less, and required more feed per lb of gain compared to pigs allowed 8, 10, and 12 ft2. Pigs permitted 8, 10, and 12 ft2 were similar in rate of gain, feed consumption, and feed efficiency, suggesting that 8 ft2 is adequate space for the finishing pig, if pens are topped out as pigs individually reach 250 lb. If pigs are fed to a pen average of 250 lb without removing pigs individually, 10 ft2 is required to maximize performance, as reported in Report of Progress 581. In this trial, space allowance of 6 ft2/pig impaired pigs performance from 120 to 200 lb. These results have been observed in previous studies, suggesting that finishing pigs need a minimum of 8ft2 in the finishing phase.
Keywords: Swine; G-F; Performance; Space; Heavy wt.